(untitled) (Conferencea, 2022)
The article emphasizes that pedagogical activity is directly related to his professional skills, as well as the need to set goals in the application of innovative educational technologies, to achieve guaranteed results, to take into account the individual and age-specific characteristics of each student. the need to focus on the problem of goal setting, the need to take into account the individual and age-specific characteristics of each student with a thorough knowledge of the methods of psychological influence.